2009
DOI: 10.1002/stem.4
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Skeletal Muscle Regeneration in a Rat Skeletal Muscle Injury Model by Local Injection of Human Peripheral Blood-Derived CD133-Positive Cells  

Abstract: Muscle injuries in sport activities can pose challenging problems in traumatology and sports medicine. The best treatment for muscle injury has not been clearly established except for the conservative treatment that is routinely performed. We investigated the potential of human adult CD1331 cells to contribute to skeletal muscle regeneration in an athymic rat model. We tested whether CD1331 cells locally transplanted to the skeletal muscle lacerated models could (a) induce vasculogenesis/angiogenesis, (b) diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 56 publications
(68 reference statements)
2
71
0
1
Order By: Relevance
“…11 Briefly, female F344/NJcl-rnu/rnu athymic nude rats (9 weeks old, n = 39) were anesthetized using intraperitoneal pentobarbital sodium (50 mg/kg). The muscle belly of tibialis anterior muscle was lacerated transversely using a scalpel.…”
Section: Skeletal Muscle Injury Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Briefly, female F344/NJcl-rnu/rnu athymic nude rats (9 weeks old, n = 39) were anesthetized using intraperitoneal pentobarbital sodium (50 mg/kg). The muscle belly of tibialis anterior muscle was lacerated transversely using a scalpel.…”
Section: Skeletal Muscle Injury Modelmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Recently, we showed that transplantation of human peripheral blood CD133-expressing cells (CD133 + cells) inhibits fibrosis and improves muscle regeneration after skeletal muscle laceration. 11 Human blood CD133 + cells are wellsuited for clinical applications, because collecting these cells is safe, with limited ethical problems. However, obtaining a sufficient number of cells is the most important factor limiting clinical application, as the proportion of CD133 + cells to mononuclear cells (MNCs) in human blood is small.…”
mentioning
confidence: 99%
“…MSCs with similar properties to bone marrow-derived MSC have been isolated from trabecular bone [162], periosteum [163], synovial membrane [164], skeletal muscle [165], skin [166], pericytes [167], peripheral blood [168] and umbilical cord [169,170]. Due to their low number upon isolation, adult stem cells require in vitro expansion and modification before being employed therapeutically [63].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Many benefits of MSC transplantation are attributed to a strong paracrine capacity, including increased angiogenesis, decreased fibrosis, immunomodulation, and secretion of survival and stem cell recruitment factors [17]. Gene expression in the injury microenvironment also appears optimally altered by the presence of stem cells to promote angiogenesis and myogenesis and limit fibrosis [18]. Taking advantage of the pro-regenerative properties of stem cells to regulate endogenous tissue regeneration via this mechanism is promising for clinical intervention.…”
Section: Introductionmentioning
confidence: 99%